Clinical Profile and Outcome of Neonates Admitted to the Neonatal Care Unit in a Rural Teaching Hospital - Shrestha, Sandeep; Sindan, N.; Kayastha, N.; Karki, D.B.; Jha, K.; Thapa, S.D.; Acharya, B.D.; Gurung, D. (Journal of Karnali Academy of Health Sciences, 2018)
Introduction: Neonatal morbidity and mortality rates reflect efficiency of health services of a country. This study was conducted to identify the clinical profile, pattern of diseases and common causes of mortality and morbidity in neonates admitted to neonatology unit. Methods: The study was conducted in Neonatal Unit of Karnali Academy of Health Sciences, Jumla for a period of one year from 1st May 2017 to 30th April 2018. Data of all admitted patients were reviewed and analyzed in terms of gender, gestational age, age at presentation, weight, cause of admission and their outcome. Diagnosis was made on clinical examination, radiological findings and laboratory investigations. Data were analyzed using SPSS version 20. Results: Out of 153 neonates admitted during the study period, 2 were excluded because of deficient record. Full-term neonates were 122(80.7%) while preterm were 29 (19.3%). Low birth weight (LBW) babies were 32 (21.18%). Neonatal sepsis 91 (60.26%) was the most common cause of hospital admissions followed by meconium aspiration syndrome 21(13.9%) and prematurity 10(6.62%). Out of 151 newborns, 112 babies (74.1%) were discharged after improvement, 15(9.93%) left against medical advice, 13(8.6%) babies were referred to higher centers for intensive care and there were 9 (5.9%) mortalities and 2(1.3%) got absconded. Conclusions: The majority of neonatal morbidity is due to sepsis, prematurity and respiratory causes. All these causes are preventable to some extent and, can be effectively treated in order to reduce morbidity and mortality.